Concussion in the international ice hockey World Championships and Olympic Winter Games between 2006 and 2015. Issue 4 (1st February 2017) - Tuominen, Markku; Hänninen, Timo; Parkkari, Jari; Stuart, Michael J; Luoto, Teemu; Kannus, Pekka; Aubry, Mark
Abstract : Background: Concussions in sports are a growing concern. This study describes the incidence, injury characteristics and time trends of concussions in international ice hockey. Methods: All concussions in the International Ice Hockey Federation (IIHF) World Championships (WC) and Olympic Winter Games were analysed over 9 ice hockey seasons between 2006 and 2015 using a standardised injury reporting system and diagnoses made by the team physicians. Results: A total of 3293 games were played (169 tournaments, 1212 teams, 26 130 players) comprising 142 244 athletic game exposures. The average injury rate (IR) for concussion was 1.1 per 1000 ice hockey player-games for all IIHF WC tournaments. The IR was the highest in the men's WC A-pool tournaments and Olympic Games (IR 1.6). However, the annual IR for concussion in the men's tournaments has been lower than that in the World Junior tournaments since 2012. When a concussion occurred with contact to a flexible board, the IR was 0.2 per 1000 player games. In contrast, the IR was 1.1, if the board and glass were traditional (for the latter, RR 6.44 (95% CI 1.50 to 27.61)). In the men's tournaments, the trend of concussions caused by illegal hits decreased over the study period. After the 4th Consensus Statement on Concussion in Sport was published (2013), none of the concussed players in the men's WC returned to play on the day of injury. Conclusions: The annual risk of concussion in the men's WC has decreased during the study period. This was most likely due to a reduction in illegal hits. The risk of concussion was significantly lower if games were played on rinks with flexible boards and glass. Rink modifications, improved education and strict rule enforcement should be considered by policymakers in international ice hockey.